2018
DOI: 10.3390/challe9010003
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Nicotinamide Adenine Dinucleotide (NAD+) in Biological Systems

Abstract: NAD + has emerged as a crucial element in both bioenergetic and signaling pathways since it acts as a key regulator of cellular and organism homeostasis. NAD + is a coenzyme in redox reactions, a donor of adenosine diphosphate-ribose (ADPr) moieties in ADP-ribosylation reactions, a substrate for sirtuins, a group of histone deacetylase enzymes that use NAD + to remove acetyl groups from proteins; NAD + is also a precursor of cyclic ADP-ribose, a second messenger in Ca ++ release and signaling, and of diadenosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 95 publications
(131 reference statements)
0
8
0
Order By: Relevance
“…Finally, ADP-ribosyl protein lyase, macrodomain-containing proteins, terminal ADP-ribose protein glycohydrolase 1 (TARG 1) and ARH3 can remove the proximal ADP-ribose residue from the acceptor protein [11][12][13][14] (Figure 1). There are monoADP-ribosylation reaction and polyADP-ribosylation reaction, and they are collectively termed "ADP-ribosylation reaction", catalyzed by enzymes widely found in animals, plants and bacteria using NAD + [15]. However, this article is intended to emphasize the importance of measuring the actual amount of PAR found in vivo and to discuss the methods and the resulting PAR levels in vivo.…”
Section: What Is Polyadp-ribosylation?mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, ADP-ribosyl protein lyase, macrodomain-containing proteins, terminal ADP-ribose protein glycohydrolase 1 (TARG 1) and ARH3 can remove the proximal ADP-ribose residue from the acceptor protein [11][12][13][14] (Figure 1). There are monoADP-ribosylation reaction and polyADP-ribosylation reaction, and they are collectively termed "ADP-ribosylation reaction", catalyzed by enzymes widely found in animals, plants and bacteria using NAD + [15]. However, this article is intended to emphasize the importance of measuring the actual amount of PAR found in vivo and to discuss the methods and the resulting PAR levels in vivo.…”
Section: What Is Polyadp-ribosylation?mentioning
confidence: 99%
“…In 2013, Martello et al reported PAR levels using a modern technique of stable isotope dilution liquid chromatography-tandem mass spectrometry (LC-MS/MS) system ( Table 1). They synthesized 13 C, 15 N-labeled PAR from 13 C, 15 N-labeled NAD + and added to the sample as tracer for estimating the recovery of PAR during purification. They reported PAR levels as 0.03 pmol/10 6 PBMC and 0.05-0.1 pmol/10 6 HeLa cells.…”
Section: Measurement Of the Amount Of Par In Vivo (Ie In Cells Or mentioning
confidence: 99%
“…NAD + is a substrate used by enzymes involved in post-translational modifications; in particular, this editorial will focus on ADP ribosylation reactions, producing mono ADP ribose (MAR) and poly ADP ribose (PAR) moieties bound to proteins and nucleic acids [1][2][3]. The intracellular concentration of NAD, its degradation to nicotinamide and its rapid, temporary unavailability (especially into localized energy compartments) are of fundamental importance to cell health or death.…”
Section: Introductionmentioning
confidence: 99%
“…In the effort to have availability of NAD+ for metabolic processes, different subcellular pools of NAD+ are regulated, and free NAD+ levels control signaling by PARPs and redox metabolism [10]. The review provides a clue on the way cells are able to overcome stressful conditions in health and disease, when provided with a surplus of NAD+ [3].…”
Section: Introductionmentioning
confidence: 99%
“…Most commonly NAD functions as a redox carrier essential for growth and development. In addition, NAD functions as a signaling molecule during plant stress, inducing defenses in response to plant pathogens 3,4 . In the presence of oxidative stress NAD is readily depleted by consuming enzymes such as PARP and sirtuins to produce NAM 5,6 .…”
Section: Introductionmentioning
confidence: 99%